Molecular characterization of Escherichia coli isolates recovered from broilers with cellulitis - Anja Müller; Kathrin Schulze Bernd; Diana Seinige; Ann-Sophie Braun; Franziska Kumm; Corinna Kehrenberg (Poultry Science, 2024)
ABSTRACT: Avian cellulitis in broilers, caused by avian pathogenic Escherichia coli, is a major cause for carcass rejections during meat inspection, resulting in significant economic losses. In this study, we analysed E. coli isolates obtained from broiler chickens affected by cellulitis for their genetic relatedness and antimicrobial resistance phenotype and genotype. The objective was to determine whether there is a clonal spread or whether these clinical isolates differ. For this purpose, E. coli was isolated from swab samples collected from diseased broilers across 77 poultry farms in Germany, resulting in 107 isolates. These isolates were subjected to serotyping, PCR-based phylotyping and macrorestriction analysis with subsequent pulsed-field gel-electrophoresis for typing purposes. In addition, the presence of virulence genes associated with avian pathogenic E. coli (APEC) was investigated by PCR. Antimicrobial susceptibility of the isolates was examined by the disk diffusion method according to CLSI guidelines and subsequently, the presence of corresponding resistance genes was investigated by PCR. Typing results revealed that a significant proportion of the isolates belonged to serotype O78:K80, which is one of the major APEC serotypes. Phylogenetic grouping showed that phylogenetic group D was most commonly represented (n = 49). Macrorestriction analysis showed overall heterogenous results, however, some clustering of closely related isolates was observed. The level of antimicrobial resistance was high, with 83.8% of isolates non-susceptible to at least one class of antimicrobial agents and 40% of isolates showing resistance to at least three classes. The most frequently observed resistance was to ampicillin, mediated by blaTEM (n = 56). However, few isolates were non-susceptible to ciprofloxacin (n = 8) and none of the isolates was resistant to 3rd generation cephalosporins or carbapenems. Overall, the results show that genetically diverse APEC associated with avian cellulitis can be found among and within German poultry farms. While most isolates were antimicrobial resistant, resistance levels to high(est) priority critically important antimicrobials were low.